Assessing Student Knowledge About Disabilities and Filling the Gap: Including Disability and Accessibility Content Into the Advertising Classroom. (May 2023) - Nelson, Michelle R.; Cook, Kirby
Persons with disabilities make up at least 15% of the population, yet advertising has, until recently, virtually ignored this audience. We report findings from a survey with 126 students enrolled in advertising classes to gauge awareness, knowledge, and perceptions of disability and advertising. Results show that the majority of students were largely unfamiliar with terminology and with web accessibility guidelines; only 22% learned about disability in any class. Students believed they had some knowledge but indicated that they would like to learn more about disability and advertising for their careers. Students perceived that the advertising industry does not make enough effort to consider disability in advertising. However, they listed brands (e.g., Nike, Apple) that were doing a good job with respect to disability. Results suggest that more content related to persons with disabilities and accessibility should be included in advertising curriculum; ideas and resources are shared.